1997
DOI: 10.1108/08876049710168483
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory investigation of consumer decision making for selected professional and nonprofessional services

Abstract: Uses services classification schemes to distinguish a professional service (doctors) from two nonprofessional services (photo finishers and dry cleaners). New residents to a community evaluate profiles for each of these service providers. Uses conjoint analysis to identify the relative importance of six attributes for each service in consumers’ decision making. As expected, finds differences in the use of attributes between the professional and the two nonprofessional services. Contrary to expectations, finds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 24 publications
(26 reference statements)
0
19
0
Order By: Relevance
“…Presumably, the decision tasks are complex for consumers who hire a professional service provider to solve problems that require specialist task-related knowledge and expertise they do not have (Rouse, 1991). From the provider's viewpoint, the complexity of the decision is increased by the fact that professional services typically involve high levels of customization and client participation (Ettenson and Turner, 1997;Hausman, 2003). Customers are usually required to provide information about their tastes, budget, goals and objectives, or problem areas before a purchase decision can be made (Mills et al, 1983).…”
Section: The Purchase-decision Taskmentioning
confidence: 97%
See 1 more Smart Citation
“…Presumably, the decision tasks are complex for consumers who hire a professional service provider to solve problems that require specialist task-related knowledge and expertise they do not have (Rouse, 1991). From the provider's viewpoint, the complexity of the decision is increased by the fact that professional services typically involve high levels of customization and client participation (Ettenson and Turner, 1997;Hausman, 2003). Customers are usually required to provide information about their tastes, budget, goals and objectives, or problem areas before a purchase decision can be made (Mills et al, 1983).…”
Section: The Purchase-decision Taskmentioning
confidence: 97%
“…Despite professional service providers' influence on the purchase decisions for many products and services, this aspect of their work has been given very little consideration in literature. Research on buying behaviour in the context of services has mainly focused on the use or selection of service providers (Ettenson and Turner, 1997;Farrell and Schroder, 1999;Gallouj, 1996;Hill and Neeley, 1988). An exception is made by authors who have contributed to the 'surrogacy' literature (e.g.…”
Section: Introductionmentioning
confidence: 98%
“…A number of interviewees stressed that a leading law firm like Firm Z could not afford to have bad WOM because a good reputation is essential in maintaining its position in the marketplace. Perhaps this explains why Murray (1991), Ettenson andTurner (1997), andNam et al (2010) suggested that WOM communication is particularly important for the service industry.…”
Section: Treating Every Job Seriously Regardless Of the Sizementioning
confidence: 93%
“…Word of mouth is also critical in customers' purchase decision making (Bansal and Voyer 2000;Ettenson and Turner 1997;Gremler 1994), reduces switching behavior (Money 2004; For this reason, service companies make substantial investments in programs fostering customer referrals and communication among customers. These programs are primarily directed at the acquisition of new customers.…”
Section: Word Of Mouthmentioning
confidence: 99%